The effect of Ag photodiffusion on characteristics of Ag-CdS diode structures - Dzhafarov, TD; Serin, M; Ören, D; Süngü, B; Sadigov, MS (IOP PUBLISHING LTD, 1999)
The effect of illumination on silver diffusion in Ag-CdS diode structures at room temperature was investigated by using radiotracer technique. The effect of photostimulated Ag diffusion in CdS at room temperature (D = 1.2 x 10(-11) cm(2) s(-1)) is equivalent to thermal diffusion of silver at about 150 degrees C. The influence of silver photodiffusion on electrical, photoelectrical and optical characteristics of Ag-CdS diode structures was studied. A decrease in the photosensitivity, rectifying characteristics of Ag-CdS diode structures and an increase in the electron concentration in the near-surface region of the CdS substrate and in the junction width and optical transmission of the structure were discovered after illumination. The possible mechanisms of photostimulated silver diffusion in CdS and degradation of characteristics of Ag-CdS diode structures are considered.
Keywords: SOLAR-CELLS; Physics